Rhetorische Figuren in Baroque Poetry "Der Welt Wollust" from The Student's Perspective of German Literature Department at The Universitas Negeri Malang - Avifah, Alvi; Kurniawan, Deddy (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
Language style, known in German as rhetorische Figuren, is one of the elements of poetry and the focus of stylistics, a discipline of linguistics. This research aimed to describe rhetorische Figuren on Baroque poetry, ,,Der Welt Wollust" by Andreas Gryphius to perspective students of the German Literature Department at the State University of Malang. Baroque is a literary periodization identified in German literature. The qualitative descriptive method was used in this research. Using an open questionnaire technique, the research's data is in the form of information on the student's perspective on language style in poetry, ,,Der Welt Wollust" one of the poems of the era of Baroque. Students from the German Literature Department who have completed the courses Literaturgeschichte and Deutsche Literatur formed the research's data source. According to current data, respondents had quite broad and different viewpoints. Although opinions have been collected, the style analysis aligns with each individual's understanding and perspective.